6n(n³ – 4n² + 3) Step-by-step explanation: Given 6 – 24n³ + 18n ← factor out 6n from each term = 6n(n³ – 4n² + 3) ← which may be factored further if required

C on Edge Step-by-step explanation:

6n^4-24n^3+18n=6n[n^3-4n^2+3] 2) For more clearity I will work separatedly the expression that is inside square brackets: n^3-4n^2+3 = n^3 – n^2 -3n^2 +3 =(n^3 -n^2) – (3n^2 – 3) = n^2 ( n-1) – 3(n^2 -1) = = n^2(n-1) -3(n-1)(n+1) = (n-1)[n^2 -3(n+1)] =(n-1)[n^2 -3n -3] 3) no i will put all the factors together 6n(n-1)(n^2-3n-3)

Answer 6

Its factored form will be Step-by-step explanation: Since we have given that So, we need to factor , Now, Now, by hit and trial method, we put n=1, So, n-1 is also factor of p(n). Now, So, its factored form will be

Answer 7

6n(n – 1)(n^2 – 3n – 3). Step-by-step explanation: The GCF = 6n. 6n^4 – 24n^3 + 18n = 6n(n^3 – 4n^2 + 3) Putting n = 1 in the expression in the parentheses: (1)^3 – 4(1)^2 + 3 = 0 so n – 1 is a factor. Dividing: n – 1 ) n^3 – 4n^2 + 0n + 3 ( n^2 – 3n – 3 n^3 – n^2 -3n^2 + 0n -3n62 + 3n – 3n + 3 -3n + 3 So the factors are 6n(n – 1)(n^2 – 3n – 3).

6n(n^3-4n^2+3) Step-by-step explanation: you can take out 6n and then make sure the signs match. It is C on Edge

6n(n^3-4n^3+3) or C on e2020 Step-by-step explanation: The GCF is 6n. divide all the terms by 6n.

= 6n(n^3 – 4n^2 + 3) Step-by-step explanation: 6n^4 – 24n^3 + 18n = 6n(n^3 – 4n^2 + 3)

- I bought some roast beef, lunch meat, and it came with blood.? - January 29, 2023
- Air undergoes dielectric breakdown at a field strength of 3Mv/m. - January 29, 2023
- what does ‘you’re rad as hell’ mean? - January 29, 2023